Dynamic failure characteristics and acoustic emission response mechanism of coal mass with various coal burst liabilities - Zhijie Zhu; Peng Wang; Fei Lv (PLoS ONE, 2025)
Coal burst liability is a key influencing factor for the occurrence of impact rock burst disaster. Uniaxial compression tests were conducted on coal bodies with various coal burst liabilities to analyze the dynamic failure characteristics of typical coal bodies, dimension (fractal dimension is a measure to describe the irregular shape of complex body), and acoustic emission (AE) energy characteristics after the coal and rock failure under loading and to investigate the failure characteristics of coal bodies with various coal burst liabilities and their AE response laws. The results show that (1) the stronger the coal burst liability, the more transient and intense the failure, the faster the kinetic energy of the crushed particles, and the more apparent the brittle failure characteristics, (2) the fractal dimension values of the crushed particles of the coal specimens have a positive correlation with coal burst liability; the stronger the coal burst liability of the coal body, the higher the degree of specimen fragmentation, and the larger the fractal dimension value, and (3)the cumulative AE energy of coal bodies with various coal burst liabilities increases significantly and evolves in a “step” pattern before the stress approaches its peak. As the coal burst liability of the coal body changes from zero to strong, the cumulative AE energy experiences a longer calm period, the width of the “step” becomes narrower, and the stored energy of the coal body gradually shifts from phase dissipation to instantaneous release. The correlation between AE parameters and coal burst liability was investigated to provide an experimental basis for AE monitoring and early warning of coal or rock fracture and rock burst.